2022
DOI: 10.1038/s42003-022-03311-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical evidence that ATP inhibits the cancer biomarker human aldehyde dehydrogenase 1A3

Abstract: Human aldehyde dehydrogenase (ALDH) participates in the oxidative stress response and retinoid metabolism, being involved in several diseases, including cancer, diabetes and obesity. The ALDH1A3 isoform has recently elicited wide interest because of its potential use as a cancer stem cell biomarker and drug target. We report high-resolution three-dimensional ALDH1A3 structures for the apo-enzyme, the NAD+ complex and a binary complex with ATP. Each subunit of the ALDH1A3-ATP complex contains one ATP molecule b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Since ATP is known to chelate magnesium 32 , it is possible that the observed inhibition is due to chelation of magnesium present in the cell extracts. Whether such chelation could happen following a spike in ATP levels in vivo is unknown, though a recent structural study of ATP inhibition of a human aldehyde dehydrogenase showed a complex interplay of ATP and magnesium binding 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Since ATP is known to chelate magnesium 32 , it is possible that the observed inhibition is due to chelation of magnesium present in the cell extracts. Whether such chelation could happen following a spike in ATP levels in vivo is unknown, though a recent structural study of ATP inhibition of a human aldehyde dehydrogenase showed a complex interplay of ATP and magnesium binding 33 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ALDH-NAD + from the three pathways mentioned above was suppressed in the ZEN-treated piglets. The ALDH-NAD + was the one of ALDH [ 65 ], and its deficiency enhanced the ethanol-induced disruption of intestinal epithelial tight junctions and barrier dysfunction [ 66 ]. Therefore, we hypothesized that ZEN could cause damage to the intestine by regulating amino acid metabolic processes via inhibiting ALDH expression in weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…The aldehyde dehydrogenase (ALDH) superfamily contains 19 enzyme isoforms that catalyze the irreversible oxidation of NAD (P) -dependent aldehydes to the corresponding carboxylic acid. ALDHs act on a wide variety of aldehyde substrates, some of which are derived from lipids, for example, retinoids, steroids, and lipid peroxidation products [19]. They play important roles in several biological processes, including the oxidative stress response, lipid hormone metabolism, and cell differentiation [20].…”
Section: Discussionmentioning
confidence: 99%